Identification of the molecular target for the suppression of contact hypersensitivity by ultraviolet radiation (The Rockefeller University Press, 1989)
This study was conducted to explore the involvement of DNA damage in the suppression of contact hypersensitivity (CHS) by UV irradiation. The opossum, Monodelphis domestica, was used because cells of these marsupials have an enzyme that is activated by visible light (photoreactivating enzyme) and repairs ultraviolet radiation (UVR)- induced pyrimidine dimers in DNA. A single dose of 1,500 J/m2 of UVB (280-320 nm) radiation, representing 2 minimal erythema doses, was administered to the dorsal skin of opossums. This treatment prevented the opossums from developing a CHS response to dinitrofluorobenze (DNFB) applied either at the site of irradiation or an unirradiated site. In addition, this dose of UVR decreased the number of ATPase+ epidermal Langerhans cells in the dorsal epidermis to approximately 3% of that in unirradiated skin at the time of DNFB application. Treatment of the animals with wavelengths that activate the repair enzyme (320- 500 nm, photoreactivating light, PRL) for 120 min immediately after UV irradiation inhibited the UVR-induced suppression of CHS almost completely. Exposure to PRL before UVR did not prevent UVR-induced suppression of CHS. PRL treatment after UV irradiation also prevented the decrease in the number of ATPase+ Langerhans cells. Measurements of lesions in DNA indicated that PRL treatment removed around 85% of the UVR-induced pyrimidine dimers. These data provide direct evidence that DNA, and most likely, the pyrimidine dimer, is the primary molecular target for the UVB-induced suppression of contact hypersensitivity to haptens applied to irradiated or unexposed skin.